2010
DOI: 10.1007/s00125-010-1851-4
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of postnatally formed small beta cell aggregates to functional beta cell mass in adult rat pancreas

Abstract: Aims/hypothesis Neogenesis of beta cells and their clustering to small aggregates is a key process in prenatal development of beta cell mass. We investigated the contribution of postnatally formed small aggregates to functional beta cell mass in adult rats. Methods Conditions were defined for (1) counting total beta cell number in pancreases with relative error of <10% and (2) determining their distribution over aggregates of different size and over functionally different subpopulations. Results Pancreases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 45 publications
3
47
2
Order By: Relevance
“…In another study, donor pancreata had little or no Ki67 + insulin-positive cells, but grafts of isolated islets from such donors had 0.22 ± 0.03% Ki67 + insulinpositive cells after 4 week transplantation in immunocompromised normoglycemic mice; this level was also found in frozen human pancreas obtained at surgery [70]. An important concept recently emphasized by Chintinne et al in rodents is that, in the adult, the large β-cell population can provide a significant pool of proliferating β-cells even though the proliferation frequency (% Ki67 + cells) is lower than in neonates [8].…”
Section: Evidence Of Compensatory Expansion In the Adult Human Pancreasmentioning
confidence: 63%
See 1 more Smart Citation
“…In another study, donor pancreata had little or no Ki67 + insulin-positive cells, but grafts of isolated islets from such donors had 0.22 ± 0.03% Ki67 + insulinpositive cells after 4 week transplantation in immunocompromised normoglycemic mice; this level was also found in frozen human pancreas obtained at surgery [70]. An important concept recently emphasized by Chintinne et al in rodents is that, in the adult, the large β-cell population can provide a significant pool of proliferating β-cells even though the proliferation frequency (% Ki67 + cells) is lower than in neonates [8].…”
Section: Evidence Of Compensatory Expansion In the Adult Human Pancreasmentioning
confidence: 63%
“…After extensive counting of total β-cells at day 2-3 and 10 weeks, Chintinne et al concluded that about 30,000 β-cell clusters of less than 50 mm diameter formed during this time in male Wistar rats [8]; this represented a 14-fold increase in the number of small aggregates of insulin-positive cells. Similarly, Peng et al showed that the islet number in mice increased from about 50/pancreas at 1 week to about 900 at 2 months after which it was stable, suggesting that impressive neogenesis occurred after birth, but became undetectable by 2 months [9].…”
Section: Abbreviationsmentioning
confidence: 99%
“…1C and D). The fraction of all endogenous b cells that could be isolated and studied further in vitro was similar in neonates and 10-week-old rats and amounted to G10% of total b cell number contained in the whole pancreas (Chintinne et al 2010). Electron microscopy indicated a 32% higher crosssectional surface of 10-week-old than neonatal b cells (P!0.005, Supplementary Table 1, see section on supplementary data given at the end of this article).…”
Section: Resultsmentioning
confidence: 83%
“…In relation to total sections, 1.9% to 2.5% of each pancreas was analyzed. A minimal sample size equal to 1.22% of the total is sufficient to achieve measurement error !10% (Chintinne et al 2010). Sections were examined using a confocal microscope (A1; Nikon, Tokyo, Japan) connected to a computer with NIS elements software (Nikon).…”
Section: Morphological and Immunohistochemical Analysesmentioning
confidence: 99%